2015
DOI: 10.1161/circimaging.115.003246
|View full text |Cite
|
Sign up to set email alerts
|

Sixty-Four–Section Cardiac Computed Tomography in Mechanical Prosthetic Heart Valve Dysfunction

Abstract: Background-Distinguishing pannus and thrombus in patients with prosthetic valve dysfunction is essential for the selection of proper treatment. We have investigated the utility of 64-slice multidetector computed tomography (MDCT) in distinguishing between pannus and thrombus, the latter amenable to thrombolysis. Methods and Results-Sixty-two (23 men, mean age 44±14 years) patients with suspected mechanical prosthetic valve dysfunction assessed by transesophageal echocardiography were included in this prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 34 publications
0
56
0
1
Order By: Relevance
“…Post-TAVI leaflet thrombosis is detected by high-resolution CT in the form of limited valve opening/closure3 and hypoattenuated leaflet thickening (HALT) (figure 1). 3 4 Although no direct evidence is available, it seems certain that these signs truly indicate the adhesion of a thrombus for two reasons: both signs are ameliorated by anticoagulant therapy5 and CT delineates thrombi as low attenuation while pannus as high attenuation 6. Echocardiography too is capable of detecting limitations of valve opening/closure, leaflet thickening, increased flow velocity across the valve and increased mean pressure differences, and shows such changes 2 7 8.…”
Section: Imaging Features Of Post-tavi Leaflet Thrombosismentioning
confidence: 99%
“…Post-TAVI leaflet thrombosis is detected by high-resolution CT in the form of limited valve opening/closure3 and hypoattenuated leaflet thickening (HALT) (figure 1). 3 4 Although no direct evidence is available, it seems certain that these signs truly indicate the adhesion of a thrombus for two reasons: both signs are ameliorated by anticoagulant therapy5 and CT delineates thrombi as low attenuation while pannus as high attenuation 6. Echocardiography too is capable of detecting limitations of valve opening/closure, leaflet thickening, increased flow velocity across the valve and increased mean pressure differences, and shows such changes 2 7 8.…”
Section: Imaging Features Of Post-tavi Leaflet Thrombosismentioning
confidence: 99%
“…Both systolic (at 20% to 40% of RR interval) and diastolic phase (at 70% to 90% RR interval) are usually necessary. With these modalities, more than 90% of the valves can be accurately evaluated (6). As opposed to retrospective triggering, prospective ECG-gated protocols tend to generate less artifacts and require lesser radiation doses.…”
Section: Ct Scan Techniquementioning
confidence: 99%
“…Hounsfield unit of the lesions can be used to distinguish thromboses from panni, as panni tend to show higher attenuation. Gunduz et al [32] reported that thromboses could be distinguished from panni with high sensitivity (87.5%) and specificity (95.5%) using a cut-off point of 145 Hounsfield units. A pannus is shown as a soft tissue attenuated lesion with a circular anatomical configuration along the subvalvular area to the valve ring (Fig.…”
Section: Embolic Eventsmentioning
confidence: 99%